2018
DOI: 10.1111/nph.15114
|View full text |Cite
|
Sign up to set email alerts
|

Functional biogeography of angiosperms: life at the extremes

Abstract: Nonlinear relationships between species and their environments are believed common in ecology and evolution, including during angiosperms' rise to dominance. Early angiosperms are thought of as woody evergreens restricted to warm, wet habitats. They have since expanded into numerous cold and dry places. This expansion may have included transitions across important environmental thresholds. To understand linear and nonlinear relationships between angiosperm structure and biogeographic distributions, we integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 68 publications
3
77
0
Order By: Relevance
“…Herbaceous plants in general tend to inhabit colder and/or drier habitats compared to their woody relatives (Zanne et al, 2014(Zanne et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Herbaceous plants in general tend to inhabit colder and/or drier habitats compared to their woody relatives (Zanne et al, 2014(Zanne et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Plant ecologists interested in comparative approaches rarely focus on clades, tending instead to work at broad phylogenetic scales. Important advances have been made at these large scales in examining the evolutionary mechanisms for trait coordination along major axes of life history variation, such as the leaf economic spectrum (Ackerly & Reich, ; Wright et al ., ; Moles et al ., ; Kerkhoff et al ., ; Donovan et al ., ), freezing adaptation (Zanne et al ., , ), or mechanisms of seed dormancy (Willis et al ., ). Yet working within highly resolved lineages is often critical to deciphering the ecological causes and direction of evolutionary shifts, given that evolutionary processes occur at smaller scales where species do not exhibit the extreme phenotypes observed across the entire evolutionary tree (Scoffoni et al ., ).…”
Section: Model Clades For the Study And Integration Of Ecology And Evmentioning
confidence: 99%
“…Latitudinal shifts in the relative roles of these two temperature variables drive the formation of mixed forest. Tree species of different leaf habits can adapt and/or acclimatize to these temperature conditions differentially, which thus alter the respective competitive performance of tree species within forests and formations of our targeted mixed forest (Woodward et al 2004, Liang et al 2013, Zanne et al 2018. In other words, evergreen broad-leaved tree species and deciduous broad-leaved tree species respond to climate in unique ways, especially to temperature variables.…”
Section: Higher Occurrence Probability Of Mixed Evergreen and Deciduomentioning
confidence: 99%
“…, Zanne et al. ). Considerable research effort has revealed that the evergreenness (or deciduousness) of tree species is tightly linked with climate‐related variables.…”
Section: Introductionmentioning
confidence: 99%